10.3k views
0 votes
Solve for x Enter the solutions from least to greatest . (x - 4)(- 5x + 1) = 0 lesser x = greater x =

Solve for x Enter the solutions from least to greatest . (x - 4)(- 5x + 1) = 0 lesser-example-1
User Oligopol
by
5.3k points

1 Answer

5 votes

Answer:

lesser x =
(1)/(5)

Greater x = 4

Explanation:

Given expression is,

(x - 4)(-5x + 1) = 0

Either (x - 4) = 0

x = 4

Or (-5x + 1) = 0

5x = 1

x =
(1)/(5)

Therefore, lesser x =
(1)/(5)

Greater x = 4

User John Lin
by
5.5k points